Telework, work organisation and job quality during the COVID-19 crisis: a qualitative study - Marta Fana; Santo Milasi; Joanna Napierala; Enrique Fernández-Macías; Ignacio González Vázquez (European Commission, Joint Research Centre (JRC), 2020)
This study aims at better understanding how the massive shift to telework following the outbreak of the COVID-19 pandemic in spring 2020 affected workers' jobs and lives. In particular, we shed light on how this exogenous change had an impact on tasks content and work organisation dimensions like teamwork, routine, workers' autonomy and types and extent of supervisory control methods. Moreover, we explored both subjective and objective dimensions of job quality such as job satisfaction, motivation, changes in working time and pay, together with issues related to physical and mental health and more generally to work-life balance. In each of selected countries, 25 teleworking employees with different job profiles, family compositions, and personal characteristics were interviewed during the lockdown of spring 2020. The picture that emerges is quite multifaceted largely depending on workers' occupation and family composition, although some general patterns can be observed. After an initial period in which workers could gain more autonomy and decisional power at almost of levels of the hierarchy, during a stabilization period new forms of remote supervisory control have been put in place and contributed to a standardization of working routines. For some, working from home increased satisfaction and productivity, and allowed to better reconcile work-family duties. In contrast, others felt teleworking, and the ensuing communication through digital platforms, challenged the possibility to receive meaningful feedback and exchange ideas with co-workers and supervisors. At times, for workers with children in school age, the negative impact was aggravated by school closure and the general lockdown. Yet, and despite the many challenges of adapting to the sudden, obligatory and highintensity telework, most of the respondents agreed that teleworking has upsides, and would be willing to continue to work remotely in the future, at least occasionally. Before that, however, workers would like to seek greater clarity around their working conditions as teleworkers.
Keywords: 330; Teleworking; remote work; tasks; work organisation; job quality; COVID-19